2022
DOI: 10.1002/ijgo.14326
|View full text |Cite
|
Sign up to set email alerts
|

Existence of chronic endometritis and its influence on pregnancy outcomes in infertile women with minimal/mild endometriosis

Abstract: Objective This study aimed to evaluate the prevalence of chronic endometritis (CE) in women with minimal/mild endometriosis and to analyze whether CE affects their pregnancy outcomes. Methods This retrospective study included 201 infertile women who were diagnosed with minimal/mild endometriosis after undergoing hysteroscopy combined with laparoscopy from January 2016 to December 2018. Immunohistochemistry was used to detect CD138 and CD38, which are specific markers of plasma cells in the endometrial stroma t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
3
0
2
Order By: Relevance
“…Both EMS and CE are prevalent gynecological conditions. Moreover, CE, which is characterized by chronic in ammation of the endometrium due to pathogenic microorganisms, is a common cause of female infertility [ 14 ] . Evidence supports this claim.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both EMS and CE are prevalent gynecological conditions. Moreover, CE, which is characterized by chronic in ammation of the endometrium due to pathogenic microorganisms, is a common cause of female infertility [ 14 ] . Evidence supports this claim.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, it is not entirely clear whether CE is a risk factor or an etiologic factor of EAI. Previous studies have revealed a higher CE frequency in patients with EMS compared to those without the disease [13][14][15] . These studies collectively indicate that the presence of EMS may be signi cantly associated with CE.…”
Section: Introductionmentioning
confidence: 85%
“…At present, antibiotic therapy is not enough to treat endometritis. This is a reproductive endocrine disorder and a chronic inflammatory disease that can lead to a decrease in fertility and productivity due to a disruption of the hormonal balance [46,168,169]. S. aureus is the main causative agent of this disease as well as other invasive infections.…”
Section: Methylseleninic Acid and Endometritismentioning
confidence: 99%
“…Пациентки с бесплодием и диагнозом «ХЭ», по сравнению с женщинами без ХЭ, демонстрируют значительно более низкую кумулятивную частоту наступления беременности (46,5 против 71,1%) и живорождения (44,2 против 63,4%) соответственно при минимальной степени инфильтрации плазматическими клетками (ПК) [7]. Вне зависимости от тяжести ХЭ наблюдается еще более высокая разница, которую приводят K. Hirata et al: наступление беременности у 30,8 против 63,0%, живорождений -у 7,7 против 51,9% соответственно [8].…”
Section: Introductionunclassified